Lack of Association Between Proton Pump Inhibitor (PPI) Use and Early Plastic Biliary Stent Occlusion - Azar, Riad R. (2011)
There are data suggesting that long-term use of PPIs may lead to small intestinal bacterial overgrowth. Plastic biliary stents are used to maintain patency of the biliary tract in a variety of benign and malignant disorders and are changed prophylactically every 3 months to avoid symptomatic stent occlusion (i.e. cholangitis or jaundice). The reasons why some patients develop early stent occlusion prior to routine stent exchange are unclear. We hypothesize that patients on PPI are more likely to develop biliary plastic stent occlusion related to increased bacterial load than patients not on PPIs.